Repeat Radiography in Monitoring Structural Changes in the Treatment of Spinal Disorders in Chiropractic and Manual Medicine Practice: Evidence and Safety - Paul A. Oakley; Niousha Navid Ehsani; Deed E. Harrison (SAGE Publishing, 2019)
There is substantial evidence for normal relationships between spine and postural parameters, as measured from radiographs of standing patients. Sagittal balance, cervical lordosis, thoracic kyphosis, lumbar lordosis, pelvic tilt, and the more complex understanding of the interrelations between these essential components of normal stance have evolved to where there are known, established thresholds for normalcy. These spinal parameters are reliably measured from X-ray images and serve as goals of care in the treatment of spine and postural disorders. Initial and follow-up spinal imaging by X-ray is thus crucial for the practice of contemporary and evidence-based structural rehabilitation. Recent studies have demonstrated that improvement in the spine and posture by nonsurgical methods offers superior long-term patient outcomes versus conventional methods that only temporarily treat pain/dysfunction. Low-dose radiation from repeated X-ray imaging in treating subluxated patients is substantially below the known threshold for harm and is within background radiation exposures. Since alternative imaging methods are not clinically practical at this time, plain radiography remains the standard for spinal imaging. It is safe when used in a repeated fashion for quantifying pre-post spine and postural subluxation and deformity patterns in the practice of structural correction methods by chiropractic and other manual medicine practices.